A panel of real-time PCR assays for the detection of Bourbon virus, Heartland virus, West Nile virus, and Trypanosoma cruzi in major disease–transmitting vectors. (November 2021) - Warang, Anushri; Zhang, Michael; Zhang, Shuping; Shen, Zhenyu
Vector-borne pathogens, such as Bourbon virus (BRBV), Heartland virus (HRTV), West Nile virus (WNV), and Trypanosoma cruzi (TCZ) are a great threat to public health and animal health. We developed a panel of TaqMan real-time PCR assays for pathogen surveillance. PCR targets were selected based on nucleic acid sequences deposited in GenBank. Primers and probes were either designed de novo or selected from publications. The coverages and specificities of the primers and probes were extensively evaluated by performing BLAST searches. Synthetic DNA or RNA fragments (gBlocks) were used as PCR templates in initial assay development and PCR positive controls in subsequent assay validation. For operational efficiency, the same thermocycling profile was used in BRBV, HRTV, and WNV reverse-transcription quantitative PCR (RT-qPCR) assays, and a similar thermocycling profile without the initial reverse-transcription step was used in TCZ qPCR. The assays were optimized by titrating primer and probe concentrations. The analytical sensitivities were 100, 100, 10, and 10 copies of gBlock per reaction for BRBV (Cq = 36.0 ± 0.7), HRTV (Cq = 36.6 ± 0.9), WNV (Cq = 35.5 ± 0.4), and TCZ (Cq = 38.8 ± 0.3), respectively. PCR sensitivities for vector genomic DNA or RNA spiked with gBlock reached 100, 100, 10, and 10 copies per reaction for BRBV, HRTV, WNV, and TCZ, respectively. PCR specificity evaluated against a panel of non-target pathogens showed no significant cross-reactivity. Our BRBV, HRTV, WNV, and TCZ PCR panel could support epidemiologic studies and pathogen surveillance.